2011
DOI: 10.1177/070674371105601207
|View full text |Cite
|
Sign up to set email alerts
|

Effectively Working on Rehabilitation Goals: 24-Month Outcome of a Randomized Controlled Trial of the Boston Psychiatric Rehabilitation Approach

Abstract: The results suggest that PR is effective in supporting patients with SMI to reach self-formulated rehabilitation goals and in enhancing societal participation, although no effects were found on the measures of functioning, need for care, and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 36 publications
1
74
2
1
Order By: Relevance
“…In this programme, illness management is defined as professional‐based interventions designed to help individuals collaborate with healthcare professionals in the treatment of their mental illness, reducing their susceptibility to relapses and allowing them to cope more effectively with their symptoms (Swildens et al . ). The meaning of recovery refers to not only relief from symptoms, which is viewed as medical recovery but also social success and personal accomplishment in areas that the person defines as important which is viewed as personal recovery (Swildens et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this programme, illness management is defined as professional‐based interventions designed to help individuals collaborate with healthcare professionals in the treatment of their mental illness, reducing their susceptibility to relapses and allowing them to cope more effectively with their symptoms (Swildens et al . ). The meaning of recovery refers to not only relief from symptoms, which is viewed as medical recovery but also social success and personal accomplishment in areas that the person defines as important which is viewed as personal recovery (Swildens et al .…”
Section: Introductionmentioning
confidence: 97%
“…In addition, its psycho‐education component was also found to be particularly effective in increasing knowledge about mental illness, social and coping skills (Swildens et al . ). Similarly, studies of behavioural tailoring which included simplifying the medication regime demonstrated its effectiveness in improving the taking of medication as prescribed (Buchanan et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…2009), and more hopeful results can be expected (Twamley et al . 2003, van Os & Kapur 2009, Swildens et al . 2011).…”
Section: Introductionmentioning
confidence: 99%
“…O fato de o paciente psiquiátrico relatar mais ou menos necessidades e de estas estarem ou não sendo supridas têm relação direta com o cuidado oferecido (Wiersma et al, 2009;Swildens et al, 2011). …”
Section: Avaliação De Necessidades Dos Pacientesunclassified